Carbapenem Resistance of OXA-48 Gene Coding in Klebsiella Pneumoniae and Escherichia Coli - Parisa, Nita; Fitrizal, Muhammad; Amalia, Ella (Annals of Mechnikov’s Institute, 2021)
Introduction: Bacteria that treated with antibiotics has ability to adapt or mutate due to form a defend mechanism. OXA-48 produces isolate that have ability as a resistance to drugs and all β-lactam, including cephalosporin, cephamycin, monobactone, and carbapenem. This study aims to identify the availability of OXA-48 gene as Carbapenem resistance in Klebsiella pneumonia (K.pneumoniae) and Escherichia coli (E.coli) from patient in Dr. Mohammad Hosein Hospital in Palembang, Indonesia. Method: The isolate bacteria from patients in Dr. Mohammad Hosein Hospital who infected with K.pneumoniae and E.coli in September until November 2017 were identified using Vitek 2 Compact. Polymerase Chain Reaction (PCR) used to detect the presence of bla OXA-48 to compare the pattern of antibiotic resistance. Result: The result showed that from 24 samples, there was 1 sample (4.7%) who positive with OXA-48 gene from K.pneumoniae bacteria and no positive gene found in E.coli bacteria. While the rest of the samples (95.3%) had negative OXA-48 gene. Conclusion: Therefore, the OXA-48 gene was only identified in K.pneumoniae. DOI: 10.5281/zenodo.4657761